Field, capital and the policing habitus: Understanding Bourdieu through the NYPD’s post-9/11 counterterrorism practices - Quinlan, Tara Lai (Criminology & criminal justice, 2021)
This article extends existing Bourdieusian theory in criminology and security literature through examining the practices of the New York City Police Department (NYPD) in the post-9/11 counterterrorism field. This article makes several original contributions. First, it explores the resilient nature of the policing habitus, extending Bourdieusian criminological findings that habitus are entrenched and difficult to change. Second, this article examines the way the resilient habitus drives subordinate factions to displace dominant factions in a field’s established social hierarchy through boundary-pushing practices, a concept previously unexamined in Bourdieusian criminology. Drawing on original documentary analysis, this article uses the illustrative example of the NYPD’s post-9/11 counterterrorism practices, exploring how it sought to displace the existing social structure by using its aggressive policing habitus and an infusion of ‘War on Terror’ capital to challenge the dominant position of the FBI in the post-9/11 counterterrorism field. The NYPD’s habitus driven counterterrorism practices were novel and unprecedented, creating strain with both the FBI and local communities.